Percutaneous nephrolithotomy access by urologist or interventional radiologist: practice and outcomes in the UK. (21st March 2017) - Armitage, James N.; Withington, John; Fowler, Sarah; Finch, William J. G.; Burgess, Neil A.; Irving, Stuart O.; Glass, Jonathan; Wiseman, Oliver J.; ,
Abstract : Objective: To compare outcomes of urologist vs interventional radiologist (IR) access during percutaneous nephrolithotomy (PCNL) in the contemporary UK setting. Patients and Methods: Data submitted to the British Association of Urological Surgeons PCNL data registry between 2009 and 2015 were analysed according to whether access was obtained by a urologist or an IR. We compared access success, number and type of tracts, and perceived and actual difficulty of access. Postoperative outcomes, including stone‐free rates, lengths of hospital stay and complications, including transfusion rates, were also compared. Results: Overall, percutaneous renal access was undertaken by an IR in 3453 of 5211 procedures (66.3%); this rate appeared stable over the entire study period for all categories of stone complexity and in cases where there was predicted or actual difficulty with access. Only 1% of procedures were abandoned because of failed access and this rate was identical in each group. IRs performed more multiple tract access procedures than urologists (6.8 vs 5.1%; P = 0.02), but had similar rates of supracostal punctures (8.2 vs 9.2%; P = 0.23). IRs used ultrasonograhpy more commonly than urologists to guide access (56.6% vs 21.7%, P < 0.001). There were no significant differences in complication rates, lengths of hospital stay or stone‐free rates. Conclusions: Our findings suggest that favourable PCNL outcomes may be expected where access is obtained by either a urologist or an IR, assuming that they have received the appropriate training and that they are skilled and proficient in the procedure.